KEKERASAN ALA KAPITALISME Sebuah Telaah atas Buku Violence and Democratic Society - Alami, Athiqah Nur (Pusat Penelitian Politik, 2006)
The rise o f capitalism at the present does not mark it as a glorious ideology. Capitalism has many dark sides that we should aware. One o f the dark sides that is worth to be noticed is the emergence o f violence against human that happened to maintain the existence o f Capitalism itself The Violence has various forms, direct violence and indirect violence. Each form o f the violence brings conseguence that is often disrespect the universal human rights.